Análisis multitemporal de cambios en la cobertura vegetal y en el espejo de agua del Humedal Laguna de la Herrera entre 1962, 2019 y 2023 (2023)
The use of geoinformation technologies allows us to better understand what is happening in our immediate environment. This work addresses the problem related to the reduction of the plant area and the water body presented by the Laguna La Herrera Wetland in the municipality of Mosquera, Cundinamarca. An analysis is made from the year 1962, date before the beginning of the extractive activities of the quarries in front of the Laguna; from the year 2019, the date before the recovery activities and finally from the current time 2023 where the CAR Regional Autonomous Corporation is in the process of recovering the wetland.